Carbon nanotubes and graphene as emerging candidates in neuroregeneration and neurodrug delivery - John AA (Dove Medical Press, 2015)
Agnes Aruna John,1 Aruna Priyadharshni Subramanian,1 Muthu Vignesh Vellayappan,1 Arunpandian Balaji,1 Hemanth Mohandas,2 Saravana Kumar Jaganathan1 1IJN-UTM Cardiovascular Engineering Centre, Faculty of Biosciences and Medical Engineering, Universiti Teknologi Malaysia, Johor Bahru, Malaysia; 2Department of Biomedical Engineering, University of Texas at Arlington, Arlington, TX, USA Abstract: Neuroregeneration is the regrowth or repair of nervous tissues, cells, or cell products involved in neurodegeneration and inflammatory diseases of the nervous system like Alzheimer’s disease and Parkinson’s disease. Nowadays, application of nanotechnology is commonly used in developing nanomedicines to advance pharmacokinetics and drug delivery exclusively for central nervous system pathologies. In addition, nanomedical advances are leading to therapies that disrupt disarranged protein aggregation in the central nervous system, deliver functional neuroprotective growth factors, and change the oxidative stress and excitotoxicity of affected neural tissues to regenerate the damaged neurons. Carbon nanotubes and graphene are allotropes of carbon that have been exploited by researchers because of their excellent physical properties and their ability to interface with neurons and neuronal circuits. This review describes the role of carbon nanotubes and graphene in neuroregeneration. In the future, it is hoped that the benefits of nanotechnologies will outweigh their risks, and that the next decade will present huge scope for developing and delivering technologies in the field of neuroscience. Keywords: neuroregeneration, neurodegeneration, nanomedical, carbon nanotube, graphene, nanodrug delivery